2023
DOI: 10.1007/s40615-023-01610-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use Among Hospitalized Patients in Africa: A Systematic Review of Point Prevalence Studies

Abstract: Background There is paucity of data describing the rate and quality indices of antibiotics used among hospitalized patients at continental level in Africa. This systematic review evaluated the pooled prevalence, indications, and types of antibiotics used in hospitals across Africa. Methods Three electronic databases, PubMed, Scopus, and African Journals Online (AJOL), were searched using search terms. Point prevalence studies of antibiotic use in inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In our study, the proportion of antibiotic prescriptions targeting specific pathogen(s) was 3.4%, lower than global levels (9.8% to 22.3%) [ 7 , 8 , 26 ], as well as previous South African studies (8.3% to 28.8%) [ 38 , 40 ]. The low-targeted prescribing observed together with low specimen collection (11.9%) and fewer results (45.2%) in our study may be attributable to a lack of point-of-care diagnostics and inadequate laboratory capacity, which may result in inappropriate diagnosis and antibiotic therapy [ 1 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, the proportion of antibiotic prescriptions targeting specific pathogen(s) was 3.4%, lower than global levels (9.8% to 22.3%) [ 7 , 8 , 26 ], as well as previous South African studies (8.3% to 28.8%) [ 38 , 40 ]. The low-targeted prescribing observed together with low specimen collection (11.9%) and fewer results (45.2%) in our study may be attributable to a lack of point-of-care diagnostics and inadequate laboratory capacity, which may result in inappropriate diagnosis and antibiotic therapy [ 1 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 95%
“…Globally, one in three hospitalised patients receives an antibiotic, however there is global variance, with low and middle-income countries having higher ABU than high-income countries [ 7 , 8 ] and one in every two hospitalised patients in SSA receiving an antibiotic [ 1 , 8 , 9 ]. The primary cause of high ABU in SSA, in particular, can be attributed to limited hospital antibiotic stewardship programme (ASP) implementation [ 10 – 13 ], inappropriate prescribing (e.g., unnecessary prescribing, inappropriate selection when an antibiotic is indicated, and incorrect dosing, formulation, route of administration and treatment duration) and empirical prescribing due to a lack of or non-adherence to treatment guidelines and limited microbiological testing due to inadequate laboratory facilities, resulting in a vicious cycle of a causal-effect relationship between ABU and ABR development [ 1 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is not unique to Sierra Leone A recent systematic review on antibiotic use among hospitalised patients in Africa reported limited data on culture and sensitivity to guide antibiotic selection. 40 The low utilisation of culture and sensitivity in hospitals in Sierra Leone reflects the lack of laboratory capacity for microbiology methods.…”
Section: Discussionmentioning
confidence: 99%
“…There are few data describing the rate and quality indices of antibiotics used in hospitalised patients in LMICs especially in Africa. However, the few data show that the prevalence of antibiotic use in hospital settings in Africa is higher than the prevalence reported in hospital settings in the other continents [43]. Broad-spectrum antibiotics such as ceftriaxone and fluoroquinolones are antibiotics commonly prescribed in hospitalised patients in Africa [43].…”
Section: Administering the Appropriate Antibioticmentioning
confidence: 99%
“…However, the few data show that the prevalence of antibiotic use in hospital settings in Africa is higher than the prevalence reported in hospital settings in the other continents [43]. Broad-spectrum antibiotics such as ceftriaxone and fluoroquinolones are antibiotics commonly prescribed in hospitalised patients in Africa [43]. SAP is the second most common indication for antibiotic use in African hospital settings.…”
Section: Administering the Appropriate Antibioticmentioning
confidence: 99%